EFEKTIFITAS VIDEO EDUKASI KESPROJA(KESEHATAN REPRODUKSI REMAJA) TERHADAP PENGETAHUAN DAN SIKAP REMAJA - Kuswanto, Kuswanto; Ristiana, Ristiana (Journal of Midwifery Science: Basic and Applied Research, 2024)
Reproductive health is a state of physical, mental, and social well-being, intact, not just free of disease or disability in all aspects related to the reproductive system, its functions, and processes. The aspect of reproductive health itself includes the reproductive system, adolescent growth and development, family planning, HIV and AIDS and other STDs. This study aims to determine the influence of KESPROJA video media on the level of knowledge and attitudes of adolescents towards Reproductive Health.This research method is a quasi experiment or pseudo-experiment with a Quasi Experiment One Group Pretest Posttest Design design. The population of all Level 1 students of the DIII Midwifery Study Program in Blora is 52 students. The side technique used is total side.The results of the study on the effectiveness of KESPROJA educational videos on adolescents' knowledge and attitudes showed that p-value = 0.001 (<0.05) for the level of knowledge and p-value = 0.003 (<0.05) for attitudes.Â  So it can be concluded that there is an influence of KESPROJA educational videos on the knowledge and attitudes of adolescents.Advice for adolescents is to increase motivation to gain knowledge about adolescent reproductive health, both organized by health workers and those that can be obtained by themselves through other social media.Â